Ghana : Country Environmental Analysis - World Bank (Washington, DC, 2012)
The Ghana Country Environment Analysis (CEA) has thus been formulated to assist the Government of Ghana and its development partners to: (a) assess the country's environmental priorities in key sectors, the environmental implications of key economic and sector policies, and the country's institutional capacity to address them; and (b) find practical management, institutional, and policy solutions to handle issues of natural resource management, environmental degradation, and sustainability of growth. Based on the results of the sectoral analysis, the key messages of the CEA can be summarized as follows: strengthening environmental governance is key to ensuring that natural resources contribute to greater wealth and sustainable growth; removing policy, regulatory, and institutional bottlenecks is crucial for reducing vulnerability of the poor in both rural and urban areas; reinforcing coordination and dialogue to mainstream ENRM is critical; and ministries, departments, and agencies in all the natural resource and environment sectors face common challenges.